EDUKASI DETEKSI DINI PENYAKIT PARKINSON PADA KADER PUSKESMAS DALAM RANGKA HARI PARKINSON SEDUNIA - Ilsa Hunaifi; Herpan Syafii Harahap; M Galvan Sahidu; Diayanti Tenti Lestari; Setyawati Asih Putri; Stefani Elizabeth Gunawan; Nyoman Ayu Susilowati (Jurnal Abdi Insani, 2022)
Parkinson's is a degenerative disease caused by the degeneration of dopaminergic neurons in the Substantia Nigra. The disease affects 1-2 per 1000 population and is estimated to double by 2040. Most of the patients don’t get adequate services and treatment in developing countries so the quality of life decreases. To increase awareness of the symptoms and signs of Parkinson's, it is necessary to involve the community in early detection. For this reason, education about the early detection of Parkinson's is needed for health cadres in Primary Health Care to reduce morbidity. This community engagement aims to provide education about the definition, signs and symptoms and how to early detection of Parkinson's disease to primary health care cadres to improve adequate health services for the patients. This community engagement was carried out at the Tanjung Karang Primary Health Care. The education method uses Powerpoint slides and video. Participants were given a pre-test, then continued with education about Parkinson's disease, and the last passed a post-test for participants 20 women participants took part in this event. Education begins with a pre-test with 10 questions about symptoms, signs, and methods for early detection of Parkinson's disease and an average score was 60 . Participants are then given the material on definitions, symptoms, early signs, how to do early detection of Parkinson's disease, and the role they can play as cadres in Primary Health Care. The education ended with a post- test. 17 participants (85%) was increased their knowledge and an average score of 89. Communication, information, and education is a solution to increase knowledge for detection Parkinson's disease in Primary Health Care cadres.